THE RELATIONSHIP BETWEEN UNDERHAND PASS TESTS AND UNDERHAND PASS SKILLS ABILITY DURING THE GAME (TUNAS MUDA UNESA ON WOMEN VOLLEYBALL CLUB) - TAUFIQ, (Jurnal Prestasi Olahraga, 2013)
This research aims to find out the relationship between underhand pass tests with underhand pass skills ability during playing game on women volleyball club Tunas Muda UNESA. In addition to calculate how big the relationship between underhand pass test with underhand pass skills ability are during playing game on women volleyball club Tunas Muda UNESA. The type of this research is quantitative research with a correlation approach. The subjects of this study were 12 women who are the main player of women volleyball club Tunas Muda UNESA. The research was conducted at GOR Bima UNESA. The results were obtained from the calculation was r = 0.760 which was consulted with r table, previously had been decided the degrees of freedom that was df = N-2, it mean df = 12-2 so df = 10, with a significance level of 5% which was obtained r table as big as 0.632. Thus, the r count was greater than r table (0.760> 0.632). It could be said that correlation or contribution of underhand pass tests to underhand pass skills ability during playing game on women volleyball club Tunas Muda UNESA was significant. From the calculation of the coefficient of determination as big as 57.76%, we can conclude that underhand pass skill ability can influence or affect the ability of the passing skills for female player at volleyball club Tunas Muda UNESA. Keywords: volleyball, skills, underhand pass